Spontaneous splenic rupture associated with scrub typhus: a case report - Hong Pil Hwang; Kyoung Min Kim; Hyojin Han; Jeong-Hwan Hwang (Infectious Diseases of Poverty, 2024)
Abstract Background Scrub typhus, an acute febrile disease with mild to severe, life-threatening manifestations, potentially presents with a variety of complications, including pneumonia, acute respiratory distress syndrome, cardiac arrhythmias (such as atrial fibrillation), myocarditis, shock, peptic ulcer, gastrointestinal bleeding, meningitis, encephalitis, and renal failure. Of the various complications associated with scrub typhus, splenic rupture has rarely been reported, and its mechanisms are unknown. This study reports a case of scrub typhus-related spontaneous splenic rupture and identifies possible mechanisms through the gross and histopathologic findings. Case presentation A 78-year-old man presented to our emergency room with a 5-day history of fever and skin rash. On physical examination, eschar was observed on the left upper abdominal quadrant. The abdomen was not tender, and there was no history of trauma. The Orientia tsutsugamushi antibody titer using the indirect immunofluorescent antibody test was 1:640. On Day 6 of hospitalization, he complained of sudden-onset left upper abdominal quadrant pain and showed mental changes. His vital signs were a blood pressure of 70/40 mmHg, a heart rate pf 140 beats per min, and a respiratory rate of 20 breaths per min, with a temperature of 36.8 °C. There were no signs of gastrointestinal bleeding, such as hematemesis, melena, or hematochezia. Grey Turner's sign was suspected during an abdominal examination. Portable ultrasonography showed retroperitoneal bleeding, so an emergency exploratory laparotomy was performed, leading to a diagnosis of hemoperitoneum due to splenic rupture and a splenectomy. The patient had been taking oral doxycycline (100 mg twice daily) for 6 days; after surgery, this was discontinued, and intravenous azithromycin (500 mg daily) was administered. No arrhythmia associated with azithromycin was observed. However, renal failure with hemodialysis, persistent hyperbilirubinemia, and multiorgan failure occurred. The patient did not recover and died on the fifty-sixth day of hospitalization. Conclusions Clinicians should consider the possibility of splenic rupture in patients with scrub typhus who display sudden-onset abdominal pain and unstable vital signs. In addition, splenic capsular rupture and extra-capsular hemorrhage are thought to be caused by splenomegaly and capsular distention resulting from red blood cell congestion in the red pulp destroying the splenic sinus. Graphical abstract